Art As Emotional Catharsis: Analyzing Creative Expression In Victoria Chang’s Poem With My Back To The World - Nurfinah Nurfinah; Dahlia D. Moelier; Sudirman Maca (Fakultas Sastra, Universitas Bosowa, 2025)
This research aims to analyze the form of emotional expression found in Victoria Chang’s poem collection With My Back to The World and to understand how Chang incorporates art of emotional catharsis. Using Aristotle’s theory of catharsis and Freud’s psychoanalytic approach, the research highlights how deep emotional experiences such as loss, alienation, trauma, and sorrow are transformed into creative expression. Chang’s poems are filled with visual imagery and metaphors that reflect inner conflict and silence, as seen in lines like “I painted silence” and “I turned my back to the world”. The research applies a qualitative descriptive that demonstrates Chang’s work conveys personal pain and creates a reflective space for readers. Her creative process illustrates how art can serve as a means to express emotions that are difficult to articulate verbally, while also offering psychological healing for both the poet and the audience. Therefore, Chang’s poetry can be understood as a medium through which traumatic experiences are processed and reimagined, positioning art as a powerful tool in the journey of emotional recovery.